Risk-Induced Trait Responses and Non-consumptive Effects in Plants and Animals in Response to Their Invertebrate Herbivore and Parasite Natural Enemies - Koprivnikar, Janet; Rochette, Alicia; Forbes, Mark R. (Frontiers in Ecology and Evolution, 2021)
Predators kill and consume prey, but also scare living prey. Fitness of prey can be reduced by direct killing and consumption, but also by non-consumptive effects (NCEs) if prey show costly risk-induced trait responses (RITRs) to predators, which are meant to reduce predation risk. Recently, similarities between predators and parasites as natural enemies have been recognized, including their potential to cause victim RITRs and NCEs. However, plant-herbivore and animal host-parasite associations might be more comparable as victim-enemy systems in this context than either is to prey-predator systems. This is because plant herbivores and animal parasites are often invertebrate species, which are typically smaller than their victims, generally cause relatively lower lethality, and allow for further defensive responses by victims after consumption begins. Invertebrate herbivores can cause diverse RITRs in plants through various means, and animals also exhibit a range of RITRs to increased risk of parasitism. This synthesis aims to broadly compare these two enemy-victim systems by highlighting the ways in which plants and animals perceive threat and respond with induced victim trait responses that are varied, but can each serve as pre-emptive defense against invertebrate enemies. We also review evidence that RITRs are costly in terms of reducing victim fitness or abundance, demonstrating how work with one victim-enemy system can inform the other with respect to the frequency and magnitude of RITRs and possible NCEs. We particularly highlight gaps in our knowledge about plant and animal host responses to their invertebrate enemies that may guide directions for future research. Comparing how potential plant and animal victims respond pre-emptively to the threat of consumption via RITRs will help to advance our understanding of natural enemy ecology and may have utility for pest and disease control.